2016
DOI: 10.5194/amt-9-5135-2016
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic correction of particle concentrations measured by underwing probes on fast-flying aircraft

Abstract: Abstract. Particle concentration measurements with underwing probes on aircraft are impacted by air compression upstream of the instrument body as a function of flight velocity. In particular, for fast-flying aircraft the necessity arises to account for compression of the air sample volume. Hence, a correction procedure is needed to invert measured particle number concentrations to ambient conditions that is commonly applicable to different instruments to gain comparable results. In the compression region wher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…The CAS-DPOL covers the size range of 0.6-50 µm in 17 bins of varying width. The probes are described in Voigt 926 M. O. Andreae et al: Aerosol characteristics and particle production in the upper troposphere et al (2017) and probes and data correction techniques in Weigel et al (2016). Information regarding the ice particle properties was obtained from the Particle Habit Imaging and Polar Scattering probe (PHIPS-HALO), a single-particle cloud probe that measures microphysical and angular light scattering properties of individual particles .…”
Section: Cloud Droplet and Ice Particle Measurementsmentioning
confidence: 99%
“…The CAS-DPOL covers the size range of 0.6-50 µm in 17 bins of varying width. The probes are described in Voigt 926 M. O. Andreae et al: Aerosol characteristics and particle production in the upper troposphere et al (2017) and probes and data correction techniques in Weigel et al (2016). Information regarding the ice particle properties was obtained from the Particle Habit Imaging and Polar Scattering probe (PHIPS-HALO), a single-particle cloud probe that measures microphysical and angular light scattering properties of individual particles .…”
Section: Cloud Droplet and Ice Particle Measurementsmentioning
confidence: 99%
“…An analysis of ice particle interarrival times (Field et al, 2003) showed no indication of particle shattering on the CAS probe inlet during contrail penetrations, as expected in the absence of large ice particles. Measured ice particle number concentrations, N m , are based on a CAS sample area of 0.21 mm 2 , as determined by laboratory calibrations, and a calculation of the sample volume following Weigel et al (2016) using thermodynamic corrections to account for compression effects.…”
Section: Particle Measurements and Data Analysismentioning
confidence: 99%
“…The probe was operated at a 1 Hz frequency. The major sources of uncertainty for the instrument are as follows (Weigel et al, 2016): (a) uncertainty in the cross-sectional area (0.278 mm 2 ± 15 %), (b) the relatively small sample volume (cross-sectional area multiplied by aircraft speed), and (c) counting statistics for each size bin. As noted by Molleker et al (2014), the CDP uncertainty is approximately 10 %.…”
Section: Methodsmentioning
confidence: 99%